Selective Oxidation of Styrene to Benzaldehyde by Co-Ag Codoped ZnO Catalyst and H2O2 as Oxidant - Abderrazak Aberkouks; Ayoub Abdelkader Mekkaoui; Brahim Boualy; Soufiane El Houssame; Mustapha Ait Ali; Larbi El Firdoussi (Advances in Materials Science and Engineering)
Various ratio of Co-Ag supported on ZnO have been evaluated in the selective catalytic oxidation of styrene to benzaldehyde, using H2O2 as an oxidant. The catalysts were prepared by a sol-gel process and were characterized using XRD, FT-IR, TG-DTG, BET, and SEM/EDX. The performance of the prepared catalyst was investigated under different parameters such as solvent, temperature, substrate/oxidant molar ratios, reaction time, and doping percent. The Zn1−x−yAgxCoyO catalysts exhibit a good activity and a high selectivity towards benzaldehyde (95%) with the formation of only 5% of acetophenone.